Glass fiber impregnating compound as well as preparation method, product and application thereof
By optimizing the component proportion and combination of glass fiber wetting agents, the problem of inconsistent wetting agent migration and glass fiber performance is solved, and higher performance consistency and lower hair production are achieved, which improves production efficiency and mechanical properties.
Patent Information
- Application Number
- CN202411866237.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing glass fiber wetting agents migrate greatly during use, resulting in inconsistent performance of glass fibers and easy to produce hairy feathers during production, affecting the use effect.
By optimizing the proportion and combination of these components, the utilization of the wetting agent and the bundling, slip and wear resistance of the glass fiber are improved by optimizing the proportion and combination of these components.
It effectively reduces the migration of the wetting agent, improves the performance consistency of glass fibers, reduces the generation of hairs, and improves production efficiency and mechanical properties.
Smart Images

Figure BDA0005194407660000021 
Figure BDA0005194407660000041 
Figure BDA0005194407660000051
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of glass fiber sizing agents, and in particular, relates to a glass fiber plied yarn sizing agent and a preparation method, product and application thereof. Background Art
[0002] Glass fiber composite materials have the advantages of light weight, high strength, corrosion resistance, low cost, easy production, good designability, beautiful appearance and comfort, and have been widely used in various industries.
[0003] With the continuous growth of the glass fiber application market and the continuous improvement of production technology, especially the emerging LFI process in recent years, the glass fiber is in a high-speed unwinding, friction and shearing state during the jetting process, and customers have put forward higher requirements for the performance stability and consistency of glass fiber. As the main mineral accounts for more than 97% and the surface impregnation agent accounts for less than 3%, the hairiness problem has always been more prominent during the use of glass fiber.
[0004] The main reason is that the sizing system can give the glass fiber excellent bundling, smoothness and wear resistance to reduce the hairiness generated during the use of glass fiber. On the other hand, after the raw silk tube is drawn and formed, the small molecular substances in the sizing agent (such as lubricants, antistatic agents and other additives) migrate from the inside of the raw silk tube to the outside with the water molecules during the film formation process during the drying process, resulting in the enrichment of lubricants, antistatic agents and other substances on the yarns at the inner and outer ring positions of the raw silk tube, while the internal yarns are less, resulting in differences in the antistatic and smoothness of the yarns at different positions of the raw silk tube. If too much small molecular substances such as antistatic agents and lubricants are used in the design of the sizing agent, although it can make up for the loss caused by migration during the baking process, it will have a certain impact on the stiffness, temperature resistance, color, etc. of the yarn. Therefore, it is necessary to study a glass fiber sizing agent that can effectively reduce the migration of the sizing agent, give the glass fiber performance consistency, and have excellent low hairiness performance. Summary of the invention
[0005] The present application aims to provide a glass fiber impregnating agent. The glass fiber produced by coating the impregnating agent can change the physical and chemical properties of the glass fiber surface, effectively reduce the migration of the glass fiber impregnating agent, and improve the bundling, smoothness and wear resistance of the glass fiber, so that the glass fiber itself has higher performance consistency.
[0006] The sizing agent of the present application has small migration of the raw yarn tube sizing agent during production, high sizing agent utilization rate, and has the advantages of excellent bundling, smoothness, smooth yarn output, etc. The glass fiber produced by using the sizing agent has excellent smoothness and bundling, as well as less hairiness, etc. The glass fiber reinforced products (such as LFI process products) reinforced by the sizing agent have excellent yarn output speed and mechanical properties, higher production efficiency, more stable mechanical properties, and smaller dispersion.
[0007] According to a first aspect of the present application, a glass fiber sizing is provided, comprising the following components, wherein the content of each component is expressed in mass percentage as follows:
[0008]
[0009] Among them, the first film-forming agent is polyvinyl acetate, the second film-forming agent is polyurethane resin, and the mass ratio of the first film-forming agent to the second film-forming agent is 2:3-16:1; the thickener is a water-soluble organic thickener; the defoamer is an aqueous emulsion defoamer; the pH adjuster is an acid pH adjuster; the antistatic agent is an ionic antistatic agent; and the lubricant is an ionic lubricant.
[0010] Preferably, the silane coupling agent is a methacryloxysilane coupling agent and / or an aminosilane coupling agent.
[0011] Preferably, the polyvinyl acetate is acrylic acid-modified polyvinyl acetate and / or cross-linked polyvinyl acetate.
[0012] Preferably, the polyurethane resin is a polyester polyurethane resin and / or a silicone-modified polyurethane resin.
[0013] Preferably, the ionic lubricant is a polyethyleneimine polyamide salt lubricant.
[0014] Preferably, the ionic antistatic agent is a quaternary ammonium salt antistatic agent.
[0015] Preferably, the aqueous emulsion defoamer is one of polyethers, organosilicones, and silicone ether copolymers. Further preferably, the aqueous emulsion defoamer is silicone ether copolymers.
[0016] Preferably, the water-soluble organic thickener is a polyacrylic acid and / or polyurethane substance.
[0017] According to a second aspect of the present application, a method for preparing a glass fiber sizing is provided, comprising the following steps:
[0018] After adding a pH adjuster into water and stirring evenly, adding a silane coupling agent and stirring evenly to obtain a solution containing a silane coupling agent;
[0019] The first film-forming agent, the second film-forming agent, the thickener, the lubricant, the defoamer, the antistatic agent and the solution containing the silane coupling agent which are diluted with water respectively are mixed and stirred evenly to obtain the glass fiber sizing agent.
[0020] According to a third aspect of the present application, a glass fiber product produced by coating the glass fiber sizing agent is provided.
[0021] According to a fourth aspect of the present application, there is provided an application of a glass fiber sizing agent in a glass fiber reinforced plastic product.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] First, the present application optimizes the compound combination by using appropriate silane coupling agents, film formers (polyvinyl acetate and polyurethane resins), thickeners, lubricants, antistatic agents, defoamers, and pH regulators, so that the effective utilization rate of the sizing agent is high, and the glass fiber is endowed with excellent sizing agent coating ability during the production process. The utilization rate of the sizing agent is effectively improved, the waste of the sizing agent is reduced, and the production cost and hazardous waste treatment cost are reduced.
[0024] Second, when the glass fiber is coated with the impregnating agent provided in the present application, the migration of the impregnating agent is small during the production and baking film forming process, the oil content of the inner and outer ring yarns of the glass fiber raw silk tube is more stable, and the product performance consistency is higher.
[0025] Third, the glass fiber produced by coating with the impregnating agent provided in the present application has excellent bundling, smoothness and antistatic properties, has less hairiness during cutting and use, and has better process performance.
[0026] Fourth, the glass fiber produced by coating the sizing agent provided in the present application has higher yarn production efficiency due to its excellent bundling and smoothness during the LFI process production; at the same time, due to the excellent cutting and dispersion uniformity of the glass fiber and the higher product consistency, the mechanical properties of the FRP products are less discrete. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be arbitrarily combined with each other.
[0028] In some optional embodiments, the glass fiber sizing of the present application includes a pH regulator, a silane coupling agent, a first film-forming agent, a second film-forming agent, a lubricant, a thickener, a defoamer, an antistatic agent and water, and the content of each component is expressed in mass percentage as follows:
[0029]
[0030] Among them, the first film-forming agent is polyvinyl acetate, the second film-forming agent is polyurethane resin, and the mass ratio of the first film-forming agent to the second film-forming agent is 2:3-16:1; the thickener is a water-soluble organic substance; the lubricant is an ionic lubricant; the defoaming agent is an aqueous emulsion defoaming agent; the antistatic agent is an ionic antistatic agent; and the pH adjuster is an acid pH adjuster.
[0031] In some optional embodiments, the glass fiber sizing agent includes a pH regulator, a silane coupling agent, a first film-forming agent, a second film-forming agent, a lubricant, a thickener, a defoaming agent, an antistatic agent and water, and the content of each component is expressed in mass percentage as follows:
[0032]
[0033]
[0034] Among them, the first film-forming agent is polyvinyl acetate, the second film-forming agent is polyurethane resin, and the mass ratio of the first film-forming agent to the second film-forming agent is 6:5-7:1; the thickener is a water-soluble organic substance; the lubricant is an ionic lubricant; the defoaming agent is an aqueous emulsion defoaming agent; the antistatic agent is an ionic antistatic agent; and the pH adjuster is an acid pH adjuster.
[0035] In some optional embodiments, the glass fiber sizing agent includes a pH regulator, a silane coupling agent, a first film-forming agent, a second film-forming agent, a lubricant, a thickener, a defoaming agent, an antistatic agent and water, and the content of each component is expressed in mass percentage as follows:
[0036]
[0037] Among them, the first film-forming agent is polyvinyl acetate, the second film-forming agent is polyurethane resin, and the mass ratio of the first film-forming agent to the second film-forming agent is 2:1-6:1; the thickener is a water-soluble organic substance; the lubricant is an ionic lubricant; the defoaming agent is an aqueous emulsion defoaming agent; the antistatic agent is an ionic antistatic agent; and the pH adjuster is an acid pH adjuster.
[0038] In the present application, the content of pH regulator, silane coupling agent, film former, thickener, lubricant, defoamer and antistatic agent refers to the percentage of the solid mass of each component to the total mass of the impregnant.
[0039] In this application, the silane coupling agent can repair the microcrack defects of the glass fiber during the production process, and as a bridge between the inorganic glass fiber and the organic polymer, it is an important component of the sizing agent. The surface of the glass fiber is rich in hydroxyl hydrophilic groups, and the film-forming agent is a hydrophobic substance; the silane coupling agent connects the glass fiber and the film-forming agent closely through physical and chemical reactions to achieve good interface bonding, and the selection of the silane coupling agent is still the key to the strength of the glass fiber and the strength of the glass fiber reinforced products. The proportion of the silane coupling agent should be controlled within a reasonable range. If the amount of the silane coupling agent is too much, the color of the glass fiber will be yellowish, the yarn will become hard and brittle, and the hairiness will increase during production and use; if the amount is too little, the coupling effect will be insufficient, the interface bonding will be insufficient, and the overall mechanical properties of the composite material will decrease. The content of the silane coupling agent is 0.1%-1.2%, preferably 0.2%-1.0%, and further preferably 0.3%-0.8%.
[0040] In some optional embodiments, the silane coupling agent is a methacryloxysilane coupling agent and / or an aminosilane coupling agent, which can cooperate with the film-forming agent, thickener, etc. provided in the present application to effectively improve the bonding between the glass fiber and the resin matrix, so that the glass fiber reinforced composite material has better mechanical properties and stability.
[0041] In the present application, the film-forming agent, as one of the important components in the glass fiber sizing agent, has a decisive influence on the production, processing and use performance of the glass fiber, and plays a role in protecting the glass fiber from damage, improving the bundling of the glass fiber and the compatibility with the matrix resin. Selecting a suitable film-forming agent can not only ensure the bundling, stiffness and smoothness of the glass fiber in subsequent use, but also ensure that the glass fiber and the matrix resin are evenly mixed and the interface bonding is sufficient and complete, thereby improving the mechanical and low hairiness and other excellent properties of the composite product. The present application adopts two film-forming agents, the first film-forming agent is polyvinyl acetate, and the second film-forming agent is polyurethane resin. The content of the first film-forming agent and the second film-forming agent in the present application is the mass percentage of the mass of its solid components to the total mass of the sizing agent. When preparing the sizing agent, the first film-forming agent and the second film-forming agent are used to prepare the sizing agent in the form of a first film-forming agent emulsion and a second film-forming agent emulsion, respectively. At the same time, the amount of film-forming agent must be controlled within an appropriate range. Excessive use of film-forming agent can easily cause the glass fiber to penetrate slowly into the resin, while affecting the resin penetration and causing the mechanical properties of the composite material to decrease; if the amount of film-forming agent is too little, it will result in the inability to give the glass fiber good bundling and protection, resulting in more hairiness, thereby affecting the subsequent smoothness of composite material processing and the interface bonding performance between the glass fiber and the resin. The content of the first film-forming agent in this application is 2.0%-8.0%, preferably 3.0%-7.0%, and more preferably 4.0%-6.0%. The content of the second film-forming agent in this application is 0.5%-3.0%, preferably 1.0%-2.5%, and more preferably 1.0%-2.0%.
[0042] In some optional embodiments, the polyvinyl acetate is acrylic modified polyvinyl acetate and / or cross-linked polyvinyl acetate.
[0043] In some optional embodiments, the polyurethane resin is a polyester polyurethane resin and / or a silicone-modified polyurethane resin.
[0044] In some optional embodiments, the mass ratio of polyvinyl acetate to polyurethane resin is 2:3-16:1, preferably 6:5-7:1, and more preferably 2:1-6:1. The inventors have found through research that when the mass ratio of polyvinyl acetate to polyurethane resin is 2:3-16:1, the bundling, wear resistance and production smoothness of glass fiber can be well guaranteed, thereby ensuring the production processability and excellent mechanical properties of glass fiber products.
[0045] In this application, the thickener is used as a rheological additive. After adding the thickener, the rheology can be adjusted, the wetting agent is thickened, precipitation is avoided during use, and good wetting agent stability is given. Studies have found that the appropriate addition of the thickener in this wetting agent system can not only significantly improve the oiling ability of the wetting agent, but also improve the effective coating rate of the wetting agent. In addition, the migration speed of water molecules can be slowed down during the film-forming process of the original silk tube after wire drawing, and the migration of small molecules (such as antistatic agents, lubricants and other additives) in the wetting agent can be effectively reduced, and the glass fiber performance consistency of different original silk tube positions can be improved. It is also found that the compound use of thickeners, film-forming agents, and lubricants has significantly improved the clustering and smoothness of glass fibers compared to the glass fibers before addition. This has significantly improved the use efficiency, hairiness and dispersibility of LFI process products. In this application, the thickener is preferably a water-soluble organic thickener. If the thickener is added excessively, the viscosity of the sizing agent is excessively increased, and the sizing agent oil film coated on the surface of the glass fiber is too thick, which is easy to be dropped during the high-speed rotation of the wire drawing machine, causing the sizing agent utilization rate to decrease instead of increase, and at the same time, it will also greatly reduce the water volatilization rate, affecting the baking efficiency. In the present application, the content of the water-soluble organic thickener is 0.002%-0.08%, preferably 0.005%-0.06%, and further preferably 0.01%-0.05%. In some optional embodiments, the water-soluble organic thickener is a polyacrylic acid and / or polyurethane substance.
[0046] In the present application, the lubricant is mainly used to ensure the lubrication effect of glass fiber in the processes of drawing, winding and LFI process production and use. Too little lubricant content will not achieve the lubrication effect, and too much content will cause the surface of the glass fiber to be sticky and stranded, affecting the cutting dispersion of the glass fiber and having a negative impact on the mechanical properties of the glass fiber composite material. The content of the lubricant is 0.03-0.6%, preferably 0.05-0.4%, and more preferably 0.1-0.3%.
[0047] In an optional embodiment, the lubricant is a polyethyleneimine polyamide salt ionic lubricant. The lubricant used in the sizing agent of the present application can not only ensure the lubrication performance of the glass fiber, improve the wear resistance of the glass fiber, reduce the occurrence of loose and flying fibers, and facilitate the smooth progress of the wire drawing operation, but also effectively improve the performance of the glass fiber, achieve a good lubrication effect, and do not affect the cutting dispersion of the glass fiber.
[0048] In this application, the antistatic agent is mainly used to ensure the conductive effect of glass fiber during the winding production process and the LFI process production and use process, and to prevent static electricity accumulation. Too little antistatic agent content will not achieve the desired effect, affecting the dispersion of glass fiber and increasing hairiness; too much antistatic agent content will cause the glass fiber to absorb moisture, increase moisture content, and cause drawing. The content of the antistatic agent is 0.01-0.5%, preferably 0.1-0.5%, and more preferably 0.2-0.4%.
[0049] In an optional embodiment, the antistatic agent is a quaternary ammonium salt ionic antistatic agent. The antistatic agent used in the present application can ensure the antistatic performance of the glass fiber, improve the conductivity of the glass fiber, avoid the accumulation of surface charge on the glass fiber, and effectively improve the performance of the glass fiber.
[0050] In the present application, the defoaming agent is mainly used to eliminate the foam generated by the impregnating agent during the wire drawing production process due to the stirring of the storage tank and the oil return process of the oil coating tank. If the generated foam is brought into the oiler with the impregnating agent, it will affect the efficiency of the wire drawing operation and the effective application of the impregnating agent, resulting in insufficient or uneven application of the impregnating agent on the surface of the glass fiber. This will cause abnormal performance such as increased fluff of the glass fiber, low oil content, poor bundling, and decreased stiffness. Too little defoaming agent content will not achieve the defoaming effect; too much will cause the surface of the glass fiber to become sticky and stranded, affecting the cutting dispersion of the glass fiber. The content of the defoaming agent is 0.05-0.5%, preferably 0.1-0.3%, and more preferably 0.15-0.25%.
[0051] In an optional embodiment, the defoamer is one of polyether, organosilicon, and siloxane copolymer defoamers, and siloxane copolymer defoamers are more preferred. The defoamer used in the present application can effectively avoid the problem of bubbles generated by the glass fiber sizing during use.
[0052] In the present application, the pH regulator mainly plays the role of regulating the pH value of the sizing agent. Specifically, an acidic pH regulator (e.g., acetic acid) can be selected. The glass fiber sizing agent of the present application needs to be controlled to a slightly acidic environment to meet the requirements of hydrolysis of the silane coupling agent and stability of the sizing agent. The content of the pH regulator is 0.01%-0.6%, preferably 0.03%-0.4%, and more preferably 0.05-0.2%.
[0053] In the present application, water is used to dissolve each component to obtain a glass fiber sizing agent of suitable concentration, and the water content is 85.53%-97.298%, preferably 87.84%-95.515%, and further preferably 90.0%-94.19%. Among them, the water is preferably deionized water.
[0054] In some optional embodiments, the method for preparing the glass fiber sizing comprises the following steps:
[0055] After adding the pH adjuster into water and stirring evenly, adding the silane coupling agent and stirring evenly again to obtain a solution containing the silane coupling agent;
[0056] The first film-forming agent, the second film-forming agent, the thickener, the lubricant, the defoamer, the antistatic agent and the solution containing the silane coupling agent which are diluted with water respectively are mixed and stirred evenly to obtain the glass fiber sizing agent.
[0057] In some optional embodiments, the method for preparing the glass fiber sizing comprises the following steps:
[0058] 1) First add water 20-60 times the mass of the silane coupling agent into the first stirring container, then add the pH adjuster, and slowly add one or more silane coupling agents in succession under stirring at a speed of 50-500 rpm, with the interval between adding each silane coupling agent being not less than 30 min, and stir and disperse evenly until the solution is clear and there is no oil droplet on the surface of the solution;
[0059] 2) First, add 2 to 10 times the mass of the first film-forming agent into the second stirring container, add the first film-forming agent under stirring at a speed of 50-500 rpm, and stir until it is evenly dispersed;
[0060] 3) Add 2 to 10 times the mass of the second film-forming agent to the third container, add the second film-forming agent under stirring at a speed of 50-500 rpm, and stir until it is evenly dispersed;
[0061] 4) Add 10 to 50 times the amount of room temperature water as thickener to the fourth container, slowly add the thickener under stirring at a speed of 100-500 rpm, and stir until uniformly dispersed;
[0062] 5) Add 60-100°C water, 5-20 times the amount of lubricant, to the fifth container, then add the lubricant, rotate at 50-300 rpm, stir until evenly dispersed, and then return to room temperature;
[0063] 6) Add 5 to 20 times the amount of hot water at 90°C or above to the sixth container, then add the antistatic agent, at a speed of 50-300 rpm, stir until evenly dispersed, and then return to room temperature; preferably 90-100°C;
[0064] 7) Add 5 to 20 times the amount of normal temperature water as defoamer to the seventh container, slowly add the defoamer under stirring at a speed of 50-300 rpm, and stir until evenly dispersed;
[0065] 8) Add the raw materials in the first to seventh containers into the eighth mixing container, add the remaining amount of water at room temperature, stir and evenly disperse to obtain the glass fiber sizing.
[0066] Among them, normal temperature refers to 20-30℃.
[0067] In some optional embodiments, the glass fiber sizing agent is used in LFI process products, wherein the products include but are not limited to glass fiber reinforced plastic products such as automobile instrument panels, automobile roofs, and trunk covers.
[0068] In order to further illustrate the beneficial effects of the types of components and the range of component contents selected in the sizing for glass fibers of the present application, some examples of values of the components included in the sizing for glass fibers of the present application are listed below.
[0069] The specific formulas of some embodiments 1 to 16 of the sizing agent for glass fiber of the present application are shown in Table 1. The values in Table 1 are the percentages of the effective component mass to the total mass of the sizing agent. It should be pointed out that the specific types, contents and combinations of the effective components selected in Table 1 do not limit the protection scope of the present application.
[0070] Table 1 Wetting agent formulations of the embodiments
[0071]
[0072] Table 1 (Continued) Sizing agent formulations of the examples
[0073]
[0074]
[0075] In order to further illustrate the beneficial effects of the present application, the LFI glass fiber sizing agent commonly used in the sanitary ware field and sizing agents with other formulations are selected as comparative examples 1 to 4, and the content of each component in the sizing agent is expressed in mass percentage as follows:
[0076] Comparative Example 1:
[0077]
[0078]
[0079] Comparative Example 2:
[0080] Comparative Example 3:
[0081] Comparative Example 4:
[0082]
[0083]
[0084] The above embodiments and comparative examples were applied to the production of glass fibers, and the corresponding glass fibers were applied to the preparation of glass fiber composite materials. The glass fiber properties and the mechanical properties of the finally obtained LFI process molded materials were compared and tested. The results are shown in Tables 2 and 3.
[0085] Table 2 Performance test results of the infiltrates of the embodiments and comparative examples
[0086]
[0087] Table 2 (Continued) Performance test results of the wetting agents of the embodiments and comparative examples
[0088]
[0089]
[0090] From the glass fiber performance test data in Table 2, it can be seen that the glass fibers prepared using the sizing embodiments (Examples 1 to 16) provided by the present application have less hairiness, faster yarn output speed, smaller differences in the oil content of the raw yarn tubes, and lower sizing agent mobility; lower mobility means that the product has better performance stability and consistency, thus being able to meet higher customer requirements. At the same time, from the glass fiber sizing agent utilization rate comparison data, it can be seen that the glass fiber sizing agent utilization rate of the embodiment products is higher, less hazardous waste is generated, and more environmentally friendly.
[0091] Table 3 Mechanical properties of glass fiber reinforced LFI products of Examples and Comparative Examples
[0092]
[0093] Table 3 (Continued) Mechanical properties of glass fiber reinforced LFI products of Examples and Comparative Examples
[0094]
[0095] From the test data in Table 3, it can be seen that the mechanical properties of the glass fiber reinforced polyurethane composites prepared using the sizing agents provided in this application (Examples 1 to 16) are relatively excellent, and the dispersion coefficient is smaller. This is a beneficial effect produced by the reasonable sizing agent components and ratios in this application.
[0096] In summary, the wetting agent of the present application can change the physical and chemical properties of the glass fiber surface through the compound use of film-forming agent, thickener and lubricant, which can effectively reduce the migration of the wetting agent, and the glass fiber performance consistency is better; at the same time, the glass fiber has better bundling, smoothness, and less fluff. The performance of glass fiber is better and the yarn output efficiency is higher. The coated glass fiber has good compatibility with the polyurethane resin used in the LFI process, which can effectively improve the interface bonding strength between the glass fiber and the resin, and the resulting composite product has more excellent mechanical properties. Broaden the application of composite materials in the field of higher products.
[0097] The contents described above may be implemented individually or in combination in various ways, and these variations are all within the protection scope of this application.
[0098] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application is described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A glass fiber sizing agent, characterized in that: The composition comprises the following components, and the content of each component is expressed as follows in mass percentage: Among them, the first film-forming agent is polyvinyl acetate, the second film-forming agent is polyurethane resin, and the mass ratio of the first film-forming agent to the second film-forming agent is 2:3-16:1; the thickener is a water-soluble organic thickener; the defoamer is an aqueous emulsion defoamer; the pH adjuster is an acid pH adjuster; the antistatic agent is an ionic antistatic agent; and the lubricant is an ionic lubricant.
2. The glass fiber sizing agent according to claim 1, characterized in that: The silane coupling agent is a methacryloxy silane coupling agent and / or an amino silane coupling agent.
3. The glass fiber sizing agent according to claim 1, characterized in that: The polyvinyl acetate is acrylic acid-modified polyvinyl acetate and / or cross-linked polyvinyl acetate.
4. The glass fiber sizing agent according to claim 1, characterized in that: The polyurethane resin is a polyester polyurethane resin and / or an organosilicon-modified polyurethane resin.
5. The glass fiber sizing agent according to claim 1, characterized in that: The ionic lubricant is a polyethyleneimine polyamide salt lubricant.
6. The glass fiber sizing agent according to claim 1, characterized in that: The water-soluble organic thickener is polyacrylic acid and / or polyurethane.
7. The glass fiber sizing agent according to claim 1, characterized in that: The aqueous emulsion defoamer is one of polyether, organosilicon and silicone ether copolymer substances.
8. The glass fiber sizing agent according to claim 1, characterized in that: The ionic antistatic agent is a quaternary ammonium salt antistatic agent; the acid pH value adjuster is acetic acid or citric acid.
9. A method for preparing a glass fiber sizing according to any one of claims 1 to 8, characterized in that: The steps include: 1) First add water 20-60 times the mass of the silane coupling agent into the first stirring container, then add the pH adjuster, and slowly add one or more silane coupling agents in succession under stirring at a speed of 50-500 rpm, with the interval between adding each silane coupling agent being not less than 30 min, and stir and disperse evenly until the solution is clear and there is no oil droplet on the surface of the solution; 2) First, add 2 to 10 times the mass of the first film-forming agent into the second stirring container, add the first film-forming agent under stirring at a speed of 50-500 rpm, and stir until it is evenly dispersed; 3) Add 2 to 10 times the mass of the second film-forming agent to the third container, add the second film-forming agent under stirring at a speed of 50-500 rpm, and stir until it is evenly dispersed; 4) Add 10 to 50 times the amount of room temperature water as thickener to the fourth container, slowly add the thickener under stirring at a speed of 100-500 rpm, and stir until uniformly dispersed; 5) Add 60-100°C water in an amount of 5-20 times the amount of lubricant to the fifth container, then add the lubricant, rotate at 50-300 rpm, stir until evenly dispersed, and then return to room temperature; 6) Add 5 to 20 times the amount of water at 90°C or above to the sixth container, then add the antistatic agent, at a speed of 50-300 rpm, stir until evenly dispersed, and then return to room temperature; 7) Add 5 to 20 times the amount of normal temperature water as defoamer to the seventh container, slowly add the defoamer under stirring at a speed of 50-300 rpm, and stir until evenly dispersed; 8) Add the raw materials in the first to seventh containers into the eighth mixing container, add the remaining amount of water at room temperature, stir and evenly disperse to obtain the glass fiber sizing.
10. A glass fiber product produced by coating the glass fiber sizing according to any one of claims 1 to 8.
11. Use of the glass fiber sizing agent according to any one of claims 1 to 8 in LFI process products.
Citation Information
Patent Citations
Glass fiber impregnating compound capable of reducing migration rate
CN105271833A
Glass fiber impregnating compound as well as preparation method, product and application thereof
CN117447096A
Glass fiber impregnating compound as well as preparation method, product and application thereof
CN117700122A
Sizing agent for glass fiber containing metal acetate
JP2003137609A
Optical fiber coating composition, optical fiber, and preparation method therefor
WO2024235062A1